How to scientifically guide expressway construction carbon emission reduction: the establishment and application of a carbon emission accounting and evaluation system - Xiong, Moyou; Li, Yangqing; Wang, Yinsheng; Zeng, Tiesen; Wang, Jinhui; Yang, Lu (Frontiers in Environmental Science, 2025)
Amid global climate change, reducing carbon emissions from expressway construction is crucial for achieving carbon peaking and neutrality goals. However, the existing expressway carbon emission accounting and assessment methods remain inadequate, failing to accurately characterize the level of carbon emissions and hindering the systematic promotion of low-carbon emission reduction work. Thus, a systematic carbon emission accounting and evaluation system is built by defining the emission boundaries during the construction period of expressways extensively, integrating the CRITIC method and the Hemming proximity Degree theory, and combining these with the "14th Five-Year Plan." Five typical sections in Hunan Province were selected to carry out empirical research. Key findings reveal significant disparities in carbon emissions across sections: S4 and S5 were rated Grade C (high emissions), whereas S1, S2, and S3 achieved Grade B (moderate emissions). The materialization stage was identified as the dominant source, contributing over 90% of the total across all sections. Its emissions were dominated by cement production, which contributed 27.10%. And steel-related materials (e.g., carbon steel reinforcement and plain carbon steel) contributed approximately 12% each of the materialization-stage total. Besides, transportation and construction stages accounted for only 2.18% and 2.69%, respectively. Notably, the carbon loss stage caused by vegetation clearance also constituted a significant emission source, especially the shrubs and scrub in S4, where it accounted for 47.9% of the total carbon emissions from all sections during the carbon loss stage. Critical section-specific hotspots included: the extensive use of steel supports in tunnel-intensive sections such as S2; high-strength cement and prestressed steel strands in bridge-dominant sections such as S4 and S5; transport activities in S2; and substantial diesel consumption in earthwork-heavy sections such as S1 and S2. These results comprehensively assess the carbon emissions of these projects during the construction process and clarify the advantages and shortcomings of each section. The system can scientifically guide the targeted carbon emission reduction work during the expressway construction period, and provide scientific decision-making support for the preparation of expressway construction carbon emission accounting and evaluation standards.